2014
DOI: 10.2478/mper-2014-0021
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling Production Orders, Taking into Account Delays and Waste

Abstract: Accepted: 8 July 2014The article addresses the problem of determining the sequence of entering orders for production in a flexible manufacturing system implementing technological operations of cutting sheet metal. Adopting a specific ranking of production orders gives rise to the vector of delays and waste in the form of incompletely used sheets. A new method was postulated for determining the optimal sequence of orders in terms of two criteria: the total cost of delays and the amount of production waste. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…Then p(i) = max {S o − t t (i); 0} and means a delay for the execution of order z i , should it be carried out last. This problem has been presented in detail in the authors' previous paper [8].…”
Section: Determining the Sequence Of Production Orders With A Minimummentioning
confidence: 98%
See 1 more Smart Citation
“…Then p(i) = max {S o − t t (i); 0} and means a delay for the execution of order z i , should it be carried out last. This problem has been presented in detail in the authors' previous paper [8].…”
Section: Determining the Sequence Of Production Orders With A Minimummentioning
confidence: 98%
“…One of the most important planning tasks is to determine the optimal sequence of production orders [4,5]. The criterion used to assess the individual ranking is most frequently the overall lead time of production orders, the sum of delays, the cost of delays and the total profit derived from the realization of a set of pending orders [6][7][8]. The proper operation of the production system is determined by its proper cooperation with the planning subsystem.…”
Section: Introductionmentioning
confidence: 99%
“…Taking stock of performance flaws revealed that there was no record of machine stoppages or other short-comings in the process, and no standardized time tests to identify the maximum installed capacity of the plant along with bottle necks. This implies that no corrective planning and production programming is done leading to cost over-runs, delays and all kinds of waste [5].…”
Section: Introductionmentioning
confidence: 99%
“…They may appear after the schedule has been prepared, which necessitates corrections. All this makes it difficult to coordinate production in time [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%